2020
DOI: 10.1371/journal.pbio.3000837
|View full text |Cite
|
Sign up to set email alerts
|

Peli1 impairs microglial Aβ phagocytosis through promoting C/EBPβ degradation

Abstract: Amyloid-β (Aβ) accumulation in the brain is a hallmark of Alzheimer's disease (AD) pathology. However, the molecular mechanism controlling microglial Aβ phagocytosis is poorly understood. Here we found that the E3 ubiquitin ligase Pellino 1 (Peli1) is induced in the microglia of AD-like five familial AD (5×FAD) mice, whose phagocytic efficiency for Aβ was then impaired, and therefore Peli1 depletion suppressed the Aβ deposition in the brains of 5×FAD mice. Mechanistic characterizations indicated that Peli1 dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…Upon trans-activating protein (Tat), Pellino1 induces autophagy, interrupts expression of tight junction protein zonula occludens1 (ZO-1), and increases the permeability of the blood-brain barrier (BBB) by triggering K63-Ub of Beclin1 (76). Pellino1 also impairs microglial amyloid bprotein (Ab) phagocytosis through promoting CCAAT enhancerbinding protein b (C-EBPb) degradation in Alzheimer's disease (AD) (77). In Parkinson's disease, upregulation of Pellino1 by asynuclein leads to the degradation of lysosomal-associated membrane protein-2 (LAMP2) and the buildup of autophagy with decreased autophagy flux by microglial exosomes (78).…”
Section: Pellino Family In Myd88-dependent Tlr Signalingmentioning
confidence: 99%
“…Upon trans-activating protein (Tat), Pellino1 induces autophagy, interrupts expression of tight junction protein zonula occludens1 (ZO-1), and increases the permeability of the blood-brain barrier (BBB) by triggering K63-Ub of Beclin1 (76). Pellino1 also impairs microglial amyloid bprotein (Ab) phagocytosis through promoting CCAAT enhancerbinding protein b (C-EBPb) degradation in Alzheimer's disease (AD) (77). In Parkinson's disease, upregulation of Pellino1 by asynuclein leads to the degradation of lysosomal-associated membrane protein-2 (LAMP2) and the buildup of autophagy with decreased autophagy flux by microglial exosomes (78).…”
Section: Pellino Family In Myd88-dependent Tlr Signalingmentioning
confidence: 99%
“…PBDML can phagocytose Aβ to reduce the burden of Aβ in the brain, thereby improving cognitive impairment in mice [52]. Xu J et al [53] found that ubiquitin ligase (Peli1) is a key regulator of microglia phagocytosis, and targeting E3 Peli1 can reduce the level of CCAAT/enhancer binding protein (C/EBP) β and CD36 expression, thereby enhancing microglia phagocytosis. Bruton's tyrosine kinase (BTK) is another key regulator of microglia phagocytosis.…”
Section: Enhance the Phagocytosis Of Microgliamentioning
confidence: 99%
“…Although a lot of researches have been done in this field in recent years (Table 3, Ref. [40][41][42][43]47,49,51,[53][54][55]58,61,64,65,[68][69][70]75,76,[78][79][80][81][83][84][85][86][87][89][90][91][92][93][94]), many important problems still exist. At present few of these drugs are applied to clinical practice, and many researches have only been tested on animals.…”
Section: Summary and Prospectmentioning
confidence: 99%
“…The pellino-1 (peli1) is a ubiquitin E3 ligase, expressed in many kinds of nerve cells in the mouse brain, and with the highest expression level of microglia [42]. Similarly, Peli1 negatively regulates the ability of phagocytosis of microglia to Aβ, resulting in the inability of clearance of deposition, leading to the deterioration of AD [43].…”
Section: Harmful and Beneficial Effects Of Microgliamentioning
confidence: 99%